How do we estimate our own intelligence?: The Relation between the Need for Cognition, Self-estimated and Actual Intelligence - Vranić, Andrea (Array, 2005)
Researh on estimates of one's own intelligence shows that males tend to give higher IQ self-estimates than females. Also, irrespective of gender, participants tend to rate their fathers higher on IQ than their mothers. There have been reports on a modest correlation between self-estimated and actual IQ score but so far this seems to be confined to spatial intelligence. Another self-report measure, Need for Cogniton, has also been found to have a positive correlation with general intelligence. We asked a sample of Croatian university students to estimate their own psychometric intelligence and the intelligence of their parents. We investigated the relation between these self-estimates and students' actual overall IQ - g. We also tested the hypothesis that Need for Cognition would have a significant correlation with self-estimated IQ score. It is hypothesized that self-estimated IQ would be more a result of one's Need for Cognition, than of one's actual IQ score.